Need of applying and improving the artificial fécondation of trout iridescent in Greece - ΠΝΕΥΜΑΤΙΚΑΤΟΣ, Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In the present research work, we have examined the case of the utilization and efficacy of some anaesthetics, especially ethylic ether, the pharmaceutical preparation MS-222 Sandoz and the mixture LARGACTIL-FARMOTAL in the narcosis of trouts which were destined to the artificial fécondation. As it concerns the artificial fécondation applied to the trouts, we came to conclusion by de mosstrating experimentaly that it is necessary to apply the anaesthesia in order to immobilize the fish and facilitate in this way the issue fof the eggs and of the sperm. The best results were obtained with MS-222 SANDOZ dissolved in water in the proportion I: 10.000 by plunging the reproductive trouts in this dilution for 5' minutes. Secondly, from the point of vue of efficacy, comes the mixture LARGACTIL-FARMOTAL in the proportion of 0.150 gr of LARGACTIL and I gr of FARMOTAL dissolved in 10 liters of water by plunging the reproductive trouts into the dilution for 1 minute